2013
DOI: 10.1088/0957-4484/24/11/115602
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent behavior of cadmium sulfide quantum dots for gallic acid estimation

Abstract: Thioglycolic acid capped cadmium sulfide (CdS/T) quantum dots have been synthesized using wet chemistry and their optical behavior has been investigated using UV-visible absorption and fluorescence spectroscopy. The role of the capping agent, sulfide source concentration, pH and temperature has been studied and discussed. Studies showed that alkaline pH leads to a decrease in the size of quantum dots and reflux temperature above 70 °C resulted in red-shift of emission spectra which is due to narrowing of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
2
10
0
11
Order By: Relevance
“…Fluorescence studies (figure 3b, blue trace) revealed that the sharp band edge lies in the visible region at approximately 583 nm (2.1 eV). Typically, the CdS QDs show strong photoluminescence (PL) in the range of 1.6-2.5 eV with the maximum at 2.1 eV closer to near visible region, indicating that PL originates from the recombination of the caged charge carriers (electron and holes) in deep traps introduced by surface states, which is a common feature of cadmium chalcogenides [15].…”
Section: Results and Discussion (A) Characterization Of Cadmium Sulfimentioning
confidence: 99%
“…Fluorescence studies (figure 3b, blue trace) revealed that the sharp band edge lies in the visible region at approximately 583 nm (2.1 eV). Typically, the CdS QDs show strong photoluminescence (PL) in the range of 1.6-2.5 eV with the maximum at 2.1 eV closer to near visible region, indicating that PL originates from the recombination of the caged charge carriers (electron and holes) in deep traps introduced by surface states, which is a common feature of cadmium chalcogenides [15].…”
Section: Results and Discussion (A) Characterization Of Cadmium Sulfimentioning
confidence: 99%
“…It is also reported that thioglycolic acid capped CdS particles with a diameter of 3.0-4.0 nm are found to display an emission peak at 530 nm. 46 In the J-aggregate/CdS nanohybrids, however, no photoluminescence emission of CdS nanocrystals is detected, as shown in Fig. 5b.…”
Section: Resultsmentioning
confidence: 89%
“…References on CdS nanoparticles are provided for interested readers [49,265,306,307,310,[379][380][381][382][383][384][385].…”
Section: Functionalisation Of Transition Metal Sulphides: Case Studiesmentioning
confidence: 99%